2002
DOI: 10.1055/s-2002-36388
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Variants of the Serotonin2CReceptor and Neuroendocrinological Responses to the Serotonin2CReceptor Agonist m-Chlorophenylpiperazine in Healthy Male Volunteers

Abstract: The neurotransmitter serotonin (5-HT) possesses several receptors and their subtypes, some of which are polymorphic, such as the 5-HT(2C) receptor. The latter has been implicated in the control of neuroendocrine function, and has been discussed in the pathophysiology and pharmacotherapy of psychiatric disorders such as obsessive-compulsive disorder, panic disorder and bipolar affective disorder. To investigate whether the 5-HT(2C) receptor polymorphism contributes to the variation of neuroendocrinological resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Future work should include attempts at direct replication of the present finding, as well as continued elucidation of the underlying biological mechanisms. In that respect, the currently available evidence for a functional consequence of this SNP comes from reports of differential 5HTR2C function comparing the amino acid substitution of Serine for Cysteine at position 23 [6], [7], [8]. Surveys of available expression quantitative trait loci (eQTL) databases did not, however, identify significant effects of this SNP on gene expression and we found no literature reports of a regulatory role for this SNP on gene expression.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Future work should include attempts at direct replication of the present finding, as well as continued elucidation of the underlying biological mechanisms. In that respect, the currently available evidence for a functional consequence of this SNP comes from reports of differential 5HTR2C function comparing the amino acid substitution of Serine for Cysteine at position 23 [6], [7], [8]. Surveys of available expression quantitative trait loci (eQTL) databases did not, however, identify significant effects of this SNP on gene expression and we found no literature reports of a regulatory role for this SNP on gene expression.…”
Section: Discussionmentioning
confidence: 78%
“…Male carriers of the less common Ser23 C allele show a trend toward faster and stronger adrenocorticotropic hormone ACTH responses to the 5HTR2C agonist m-chlorophenylpiperazine (m-CPP) [7], as well as a different pattern of change in regional cerebral blood flow following m-CPP infusion compared to men carrying the 5HTR2C Cys23 G allele [8]. In related work [9] we recently found that rs6318 was associated with stress responses to an emotional stress task in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…HTR2C seems to scarcely impact the risk of psychosis, lack of association has been consistently detected between HTR2C variations and suicide behavior [Pooley et al, 2003;Turecki et al, 2003;Stefulj et al, 2004;Serretti et al, 2007b;Zhang et al, 2008], while sparse results could be found for depressive phenotype [Frisch et al, 1999;Lerer et al, 2001]. Along with these findings, the number of studies that found lack of association greatly dims the quality of information one can retrieve from the knowledge of the presence of a mutation in the HTR2C coding gene: for example, it has been reported in this article how HTR2C impacts the anxiety and stress related response in animal models; nevertheless, Kuhn et al [2002] failed to find an association between the widely investigated rs6318 and ACTH response after mCPP challenge in healthy subjects. With regards this last investigation, the small sample size may have biased the study toward the detection of the small ''one mutation in one gene'' impact toward the endophenotype, but more generally the lack of consistence and the gap between the neuroanatomical evidence of the relevance of the HTR2C toward the psychiatric phenotypes and the poor genetic evidence sustaining it, could be due to a wide range of reasons including the different design of the studies, the non-correspondence between inclusion and exclusion criteria, different treatment and a list of stratification factors that our group recently reviewed [Serretti et al, 2008]: that work was focused on depression, but the general meaning of it may be of interest for some other psychiatric disorders as well.…”
Section: The Evidence Coming From Genetic Association Studiesmentioning
confidence: 90%
“…Recent research indicates that the Ser23 C allele is constitutively more active than the Cys23 (Okada et al, 2004). In humans, compared to men carrying the 5HTR2C Cys23 G allele, those with the less common Ser23 C allele show a trend to faster and stronger ACTH responses to the 5HTR2C agonist mchlorophenylpiperazine (m-CPP) (Kuhn et al, 2002), as well as a different pattern of change in regional cerebral blood flow following m-CPP infusion (Kuhn et al, 2004). Cortisol response to oral m-CPP in women did not differ as a function of rs6318 (Cys23Ser) genotype (Quested et al, 1999)–a difference that could be due to X inactivation of the 5HTR2C gene variants on the X chromosome (Valley & Willard, 2006).…”
Section: Introductionmentioning
confidence: 99%